Caffeine and creatine content of dietary supplements consumed by Brazilian soccer players - Galante Inácio, S.; Vieira de Oliveira, G.; Silveira Alvares, T. (International Journal of Sport Nutrition and Exercise Metabolism, 2016)
Caffeine and creatine are ingredients in the most popular dietary supplements consumed by soccer players. However, some products may not contain the disclosed amounts of the ingredients listed on the label, compromising the safe usage and the effectiveness of these supplements. Therefore, the aim of this study was to evaluate the content of caffeine and creatine in dietary supplements consumed by Brazilian soccer players. The results obtained were compared with the caffeine content listed on the product label. Two batches of the supplement brands consumed by = 50% of the players were considered for analysis. The quantification of caffeine and creatine in the supplements was determined by a high-performance liquid chromatography system with UV detector. Nine supplements of caffeine and 7 supplements of creatine met the inclusion criteria for analysis. Eight brands of caffeine and five brands of creatine showed significantly different values (p < .05) as compared with the values stated on the label. There were no significant differences between the two batches of supplements analyzed, except for one caffeine supplement. It can be concluded that caffeine and creatine dietary supplements consumed by Brazilian soccer players present inaccurate values listed on the label, although most presented no difference among batches. To ensure consumer safety and product efficacy, accurate information on caffeine and creatine content should be provided on all dietary supplement labels.